Інноваційні вияви історичної пам’яті у філософсько-релігійних ідеях: суперечності гармонізації - Тіменик, З. І. (Lviv Polytechnic Publishing House, 2016)
На підставі спадщини українських мислителів 60-х рр. ХІХ ст. – 70-х рр. ХХ ст. розкрито інноваційні особливості історичної пам’яті стосовно обміркованих ідей. Автор зазначає, що у контексті (між)релігійних комунікацій, міждисциплінарного простору такі особливості у системі духовної культури взаємообумовлюються. Суперечності й гармонізація у виниклих процесах є об’єктивними, закономірними, бо історична пам’ять є однією із запорук у розвиткові духовно-культурної спадщини. In order to elaborate on this topic, the works of Ukrainian thinkers (60s of XIX – 70s of XX c.) are analyzing (Orest Novуts’ky, Olexy Kozlov, Nicholas Berdyaev, Sergey Bulhakov, Metropolitan Ilarion (Ohijenko), Patriarch and Cardinal Joseph Slipyj). The idea of God in the structure of man and Universe, the idea of interaction of good and evil, light and darkness become the object of our research. On the basis of the universal model “now–once” and the universal relation “God–man-God” the historical memory as an interdisciplinary space is considered. The principles of graduality–consistency, transcendence, wholeness and harmony-symphony are using as partially methodological tools. The idea of God in the structure of man and the universe is considered as the condition of the historical development of religion and also from the point of view of a pseudo-religion. The idea of interaction of good and evil, light and darkness is considered and explicated from the complex point of the problem of interaction elements in the interdisciplinary space. “The religious logics” has the real function in the context of the historical memory and supposes the introduction such new concepts as “inter-religious consciousness”, “revelation studies”. The author justifies a historical interdependence of considered principles, relations, ideas and other mental constructs. A certain harmonization of analytical and synthetic thinking at different stages of historical development of religious systems is affirmed, when an act of philosophical and historical cognition was stipulated by an act of faith. Versatility and ambiguity of processes possessing elements of harmony and synthesis are validated. The regularity of harmony of individual interreligious doctrinal of concepts and phenomenа is interpreted.
Keywords: Бог; добро-зло; ідея; істина; історико-релігійний процес; світло-темрява; темпоритміка; God; good-evil; historical and interreligious process; idea; light-darkness; temporal rhythm; truth; 291.1 : 211 : 216 (477) “1860/1970”